Perancangan dan Pembuatan Alat Simulator Radio Frequency Identification (RFID) Berbasis Arduino untuk Optimalisasi Inventaris Gudang - Pramoedya, Zafir Istawa; Darmawan, Bambang; Rahman, Aulia Zikri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Manual inventory recording in warehousing is prone to high risks of data entry errors, data loss, and operational inefficiency. This study aims to design and test an RFID simulator device based on Arduino UNO R3 and ESP32 microcontroller to simulate warehouse automation. The system design includes the development of integrated hardware and software components to form a comprehensive RFID workflow. Testing was conducted to assess reading accuracy, maximum reading distance, response time, as well as the ability to modify and delete data. The results show that the system can read tags with 100% accuracy, with a maximum range of 15 cm and an average response time of 4.83 seconds. The system also successfully performs data modification and deletion via a web interface, indicating its applicability to basic warehouse and logistics systems.